Glucose-6-Phosphate Dehydrogenase Deficiency and Malaria: A Method to Detect Primaquine-Induced Hemolysis in vitro - Allahverdiyev, Adil M.; Bagirova, Malahat; Elcicek, Serhat; Koc, Rabia Cakir; Ates, Sezen Canim; Baydar, Serap Yesilkir; Yaman, Serkan; Abamor, Emrah Sefik; Oztel, Olga Nehir (IntechOpen, 2012)
None